2008
DOI: 10.17796/jcpd.33.1.212p1q4156625122
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Management and Long-Term Follow-up of Mesiodens: A Case Report

Abstract: Supernumerary teeth are relatively common in the oral cavity and are characterized by an excessive number of teeth. The term "mesiodens" refers to a supernumerary tooth located in the midline of the maxilla between the central incisors. Mesiodens may cause a variety of pathological complications such as impaction of the maxillary central incisors, tooth retention or delayed eruption of the permanent incisors,crowding, eruption within the nasal cavity, formation of diastema, intraoral infection, root anomaly, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 1 publication
0
15
0
4
Order By: Relevance
“…Of these, almost half is found in the anterior region with the prevalence of 15% to 1.9% 11 . Among the possible causes for this positioning are the cleft palates, tumors, trauma, cleft lip, malformation and genetic factors 8 , which in the shown case were not confirmed in the anamnesis and in the clinical exams carried out. Some studies associate the alteration in the regular number of teeth to the phylogenetic reversion and hyperactivity of the dental lamina 7 and also with dichotomy of a tooth germ 6 .…”
Section: Collaboratorsmentioning
confidence: 67%
See 1 more Smart Citation
“…Of these, almost half is found in the anterior region with the prevalence of 15% to 1.9% 11 . Among the possible causes for this positioning are the cleft palates, tumors, trauma, cleft lip, malformation and genetic factors 8 , which in the shown case were not confirmed in the anamnesis and in the clinical exams carried out. Some studies associate the alteration in the regular number of teeth to the phylogenetic reversion and hyperactivity of the dental lamina 7 and also with dichotomy of a tooth germ 6 .…”
Section: Collaboratorsmentioning
confidence: 67%
“…The combination of genetic factors can also influenciate this anomaly 3,[7][8][9][10] . The studies have shown that there is a connection in the occurrence of mesiodens with the gender, which occurrs twice more in males than in females 2-3,6-7,11-12 . RGO, Rev Gaúch Odontol, Porto Alegre, v.64, n.1, p. 83-86, jan./mar., 2016 E MIRANDA et al radiographical exams were carried out.…”
Section: Introductionmentioning
confidence: 99%
“…When they do not erupt, they interfere with the eruption of permanent teeth, which may cause malocclusions. 10,35,36,37 Multiple mesiodens are less likely to erupt. 32,33,34 The purpose of this article is to describe three patients with rare cases of double maxillary mesiodens.…”
Section: -30mentioning
confidence: 99%
“…25,34 El tiempo que se toma para la erupción del diente permanente, una vez se ha realizado la exodoncia del diente supernumerario, varía entre seis meses y tres años. 10,34,35 Los factores que influyen en la erupción son: el tipo de diente supernumerario, núme-ro de dientes supernumerarios, la distancia de desplazamiento del diente permanente por erupcionar, ángulo de impactación con relación a la línea media, cantidad de formación radicular del diente permanente, estado de desarrollo radicular del diente supernumerario y el espacio disponible en la arcada para la erupción del diente permanente sin erupcionar. 27,30,33 …”
Section: -24unclassified
See 1 more Smart Citation